Equilibrium Points and Periodic Orbits of Artificial Satellite Adjacent to an Oblate and Rotating Asteroid - La Fatsa Fauzia; Dermawan Budi (Jurnal Ilmu Fisika, 2026)
Asteroids have various shapes (mostly irregular) and physical characteristics. Space missions to asteroids are becoming frequent, and a global mapping scheme is applied to collect the asteroids’ physical properties. Depending on the mission purposes, the mapping scheme can encircle the whole asteroid’s body or utilize the asteroid’s equilibrium points for the least energy consumption. Furthermore, it is essential to construct optimal trajectories to maximize the coverage and science results. Thus, an efficient mission can be achieved by devoting periodic orbits of artificial satellites around the equilibria. This study aims to construct periodic orbits related to the equilibria of an oblate shape and rotating asteroid, under the influences of gravitational and rotational potentials. Equations of motion of the satellite affected by the potentials are formulated in the Cartesian coordinate system. By acquiring mutual zero accelerations (first derivative of the potentials with respect to all directions), the equilibria are then obtained. Adjacent to the asteroid, four equilibria were revealed, and analysis of their stability showed that all of them are unstable. Despite this, some periodic orbits centered at the respective equilibria were successfully constructed using some arbitrary parameters (harmonics) that affect the coverage area for mapping the asteroid.